Enhance Some Insulation Properties of Epoxy by Using Waste Materials - Fahad, Besma M.; Naser, Afaf Abdulhussein (Al-Nahrain Journal for Engineering Sciences, 2018)
Particles filled polymer composites started to be essential because of their wide applications in addition to reducing the cost of polymer, which is a main problem. The aim of this work is studying the insulation of particulate composites resulting from the addition of filler (glass or porcelain) waste powder to reinforced epoxy matrix. Samples with and without filler were exposed to some tests to decide the influence of the filler contents on the characteristics of epoxy. Epoxy is synthesized with filler particles having (90 micron) particle sizes as reinforcement. Composites of epoxy with varying percentage (0 to 40 weights %) of filler were prepared by using hand lay-up method.  The nondestructive tests consist of thermal conductivity; ultrasonic test and water absorption test have been investigated. The composite showed an improvement in physical properties with the addition of filler according to their percentages. The result show the addition of the filler in all proportions to the epoxy increased the density of the composite, leading to the ultrasonic pulses velocity ranges between 2100 m/s and 2800 m/s.  Increase glass and porcelain percentage cause increase in density which increases the acoustic impedance. While the thermal conductivity decrease with glass powder percentages in the composite increase, unlike the increase in porcelain percentage which causes an increase in thermal conductivity. The 40% percentage of glass in the epoxy had higher effect on reduce the thermal conductivity. As well as from the results the epoxy reinforced by porcelain powder would have lower water absorption than epoxy reinforced by glass powder.